2002
DOI: 10.1038/sj.cgt.7700526
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular transfer of active HSV-1 thymidine kinase mediated by an 11-amino-acid peptide from HIV-1 Tat

Abstract: Suicide gene therapy using herpes simplex virus type -1 ( HSV -1 ) thymidine kinase ( TK ) is a widely exploited approach for gene therapy of cancer and other hyperproliferative disorders. Despite its popularity, clinical success has been so far hampered mostly by the relative inefficiency of TK gene transfer and its limited bystander effect. Here we report that fusion of TK to an 11 -amino -acid peptide from the basic domain of the HIV -1 Tat protein ( Tat11 ) imparts cell membrane translocating ability to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 51 publications
(46 reference statements)
3
27
0
Order By: Relevance
“…[4][5][6][7][8][9] PTDs can even deliver bulky molecular cargos (>100 kDa) into a wide variety of cell types. [10][11][12][13] However, to use PTDs as effective intracellular drug delivery carriers with clinical applications, it is necessary to create novel PTDs with greater protein-transduction potency than exists naturally.…”
Section: -3)mentioning
confidence: 99%
“…[4][5][6][7][8][9] PTDs can even deliver bulky molecular cargos (>100 kDa) into a wide variety of cell types. [10][11][12][13] However, to use PTDs as effective intracellular drug delivery carriers with clinical applications, it is necessary to create novel PTDs with greater protein-transduction potency than exists naturally.…”
Section: -3)mentioning
confidence: 99%
“…Limited studies have shown that PTD is conferred with transcellular property [125,141]. Indeed, this behavior is extremely valuable in delivering therapeutic proteins to surrounding cells.…”
Section: Transcellular Property Of Ptdmentioning
confidence: 99%
“…Thus, development of this approach was an important step in the establishment of TK suicide gene therapy. 236 The attachment of TATp to a water-soluble synthetic macromolecule, N-(2-hydroxypropyl)methacrylamide copolymer, resulted in the cytoplasmic and nuclear delivery of the conjugate via nonendocytotic and concentration-independent processes, as opposed to conjugates without TATp, which accumulated in only endocytotic vesicles. Furthermore, the TATp-polymer-bound anticancer drug doxorubicin was delivered inside the cytoplasm, providing the possibility for the development of polymer-based systems for the cytoplasmic delivery of therapeutic molecules.…”
Section: Delivery By Cppsmentioning
confidence: 99%